Remarkable diaries : the world's greatest diaries, journals, notebooks, & letters - Grant, R. G. (DK, 2020)
Compiles writing from the diaries of famous individuals, such as Virginia Woolf, Samuel Pepys, and Ferdinand Magellan, and provides historical information about the times in which they lived.